Low-tube-current multidetector CT for children with suspected extrinsic airway compression - Preeyacha Pacharn (2018)
OBJECTIVE. The purpose of our study was to review the technical success achieved using low-tube-current multidetector CT for the evaluation of children with suspected extrinsic airway compression and to evaluate the need for sedation during this procedure. MATERIALS AND METHODS. We reviewed all CT examinations performed for the evaluation of extrinsic airway compression during the first year after installation of a multidetector CT scanner at a pediatric hospital. We recorded the technical parameters including tube current, kilovoltage, slice thickness, mode of study, sedation technique, and amount of contrast material and noted which postprocessing techniques were applied. Studies were evaluated for timing of contrast bolus, image quality, motion artifact, need for sedation, and the diagnoses made. RESULTS. Fifty-four studies were performed in 50 patients (30 boys, 20 girls; age range, 15 days to 17 years; mean age, 2.4 years). The mean tube current was 52.2 mA (range, 30-140 mA). Thirty-four studies (63%) were performed without sedation: 12 with sedation administered under supervision of the radiologist, six with general anesthesia supervised by an anesthesiologist, and two in patients who arrived in the radiology department already intubated. Imaging quality was excellent in 35 studies (65%), diagnostic in 19 studies (35%), and poor in none. Motion artifact was present on several slices in two examinations (4%). Contrast medium administration was well-timed in 49 studies (91%), early in three studies (5%), and late in two studies (4%). Airway abnormalities were detected in 26 (48%) of the studies and included extrinsic compression by vascular anomalies (n = 14) or nonvascular masses (n = 5) and intrinsic airway disease without extrinsic compression (n = 7). CONCLUSION. Evaluation for extrinsic compression of the airway in children can be accomplished using a low-tube-current multidetector CT protocol; in most pediatric patients, the examination can be performed without sedation.